Gremo, statistika! - Erčulj, Vanja Ida; Šulc, Ajda (University of Maribor Press, 2022)
Let’s go, statistics! The textbook presents the basic statistical concepts and the calculation of descriptive statistics, and illustrates the use of statistical programs PSPP and SPSS for this purpose. It presents statistics in a contemporary way focusing on interpretation and understanding of results obtained by statistical programs. The acquired knowledge is crucial for student’s preparation of the final thesis.